Pragmatic Failures in Movie Subtitles: The Case of Kurdish Subtitles of Treasure Island (Raparin Journal of Humanities (RJH), 2024)
Pragmatic failures are critical in movie translation as they affect the message of the movie. Pragmatic failure refers to the mismatches that may occur between speakers’ intended meaning and translators’ constructed meaning. The paper aims to investigate the nature of pragmatic failures in translating movie subtitles from English into Kurdish. It attempts to identify the factors that cause pragmatic failures and find out the types of failures in the selected movie. The data of the study are taken from the transcripts of the English adventure movie Treasure Island which has been translated into Kurdish. The English source text and the Kurdish subtitles were compared to find out the types and identify the causes of pragmatic failures. The paper draws upon Thomas’s (1983) category to classify pragmatic failures. The results of the study show that both types of pragmalinguistic failure and sociopragmatic failure are found in the movie which resulted from a lack of translator’s qualification in translation, a lack of pragmatic as well as cultural knowledge of both the source and target languages. It has also been found that pragmatic failures are failures of transferring speech acts from the source language to the target language that cause a lack of proper understanding of the source message. In other words, pragmatic failures are the result of mistranslation, under-translation, and over-translation errors which cause non-equivalency between the message in the source language and the one in the target language.